Unusual Cause of Submucosal Mass in the Duodenal Bulb: Ectopic Pancreas - Tas, Adnan; Celık, Hacer (Fırat University, 2012)
Ectopic pancreas (EP) is the presence of an abnormally located focus of normally developed pancreatic tissue outside the boundaries of the orthotopic pancreas. Although EP is usually found in the upper gastrointestinal tract they also could be found anywhere in the gastrointestinal tract, pelvis and in the thorax. Here, we report an uncommon case of EP in the duodenal bulb.

Ektopik pankreas, pankreasın normal lokalizasyonu dışında saptanan pankreas dokusudur. Ektopik pankreas genellikle üst gastrointestinal sistemde saptanırken, tüm gastrointestinal sistemde, pelvis ve toraksta bulunabilir. Burada bulbusta lokalize ektopik pankreası takdim ettik.
Bulbusda Submukozal Lezyonun Nadir Nedeni: Ektopik Pankreas